Answer:
a = 21 + -7c
Step-by-step explanation:
Simplifying
[a + 7(c + -3)] = 0
Reorder the terms:
[a + 7(-3 + c)] = 0
[a + (-3 * 7 + c * 7)] = 0
[a + (-21 + 7c)] = 0
Reorder the terms:
[-21 + a + 7c] = 0
Remove brackets around [-21 + a + 7c]
-21 + a + 7c = 0
Solving
-21 + a + 7c = 0
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '21' to each side of the equation.
-21 + a + 21 + 7c = 0 + 21
Reorder the terms:
-21 + 21 + a + 7c = 0 + 21
Combine like terms: -21 + 21 = 0
0 + a + 7c = 0 + 21
a + 7c = 0 + 21
Combine like terms: 0 + 21 = 21
a + 7c = 21
Add '-7c' to each side of the equation.
a + 7c + -7c = 21 + -7c
Combine like terms: 7c + -7c = 0
a + 0 = 21 + -7c
a = 21 + -7c